Consumer awareness, trust and cultural challenges in the use of child car seats in Iran: Current status and improvement strategies - Ebrahim Zarepour Nasirabadi; Shiva Yazdani; Bahram Shirini; Mirbahador Yazdani (PLoS ONE, 2026)
Background Injuries that occur on the road are greatly affecting young children across the globe. Learning about the myths future parents may have and the barriers they may face is important. This study aimed to assess parental awareness, trust, cultural factors, and barriers related to the use and correct use of child car seats among parents of young children in Iran. Methods This cross-sectional study included approximately 750 parents of children aged 1–3 years in Tabriz, Iran. The data were collected via a structured questionnaire conducted at 19 public health centers. An expert panel confirmed content validity (CVI = 0.89; CVR range: 0.71–1.00), and internal consistency was acceptable (Cronbach’s alpha = 0.82). Data were analyzed using descriptive statistics and inferential methods, including chi-square tests, t-tests, ANOVA, and regression models. Results Although 92% of participants owned a car, only 47% owned a child car seat, and 55% reported rarely or never using one. Awareness of age and weight recommendations was high (85%), but knowledge of correct installation was lower (62%). Car seat use was significantly lower during city trips (45%) compared to out-of-city trips (82%) (d = 1.25). Consistent fastening of the child’s seatbelt during city trips was 28%. Significant predictors of fastening the seatbelt include Trust (β = 0.45), Education (β = 0.30), and Risk Perception. Major barriers included high cost (62%), lack of awareness (55%), and cultural practices such as holding children on laps (50%). Conclusion High vehicle ownership alone does not ensure child safety. Multilevel interventions combining skills-based education, affordability, product quality assurance, social norm change, and policy enforcement are needed to improve both the use and correct use of child car seats.